If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = -5 Reorder the terms: -4 + 9x = -5 Solving -4 + 9x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = -5 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = -5 + 4 9x = -5 + 4 Combine like terms: -5 + 4 = -1 9x = -1 Divide each side by '9'. x = -0.1111111111 Simplifying x = -0.1111111111
| 5x+9=x+20 | | 7d-2d+4d+3=4d | | p-.20p=120 | | 2j=4j+12 | | 104-(4x-8)=4(10-6x) | | 4s-12=-5s+51 | | 2x-26=10 | | 2*4+3n=34 | | 8r+s-7s= | | 5*3+2n=70 | | 10n-2=78 | | .375u=-15 | | 2n-2=78 | | 9x=9-81 | | 3n+12-5n=22 | | y+(-6)=-9 | | 5b-4b+b-15= | | 9+8(t-7)=6(t+5)+7 | | 4x+12=-24 | | 8y+3y= | | 37-18+8w=67 | | 2n-3=19 | | 2(2n+1)+4(n-7)=2n+8n | | 17+4y=6y-15 | | 5-3p=20 | | -11(-3-8b)=-7+7(8+12b) | | 5x-4x+x-15= | | -3+9(v+1)=5(3v+12) | | 24-2z=6 | | 7x+10=9x-10 | | 8+5(2+3x)=6(2x+9) | | 4x+x-7x= |